Jojan: a novel virus that lyses Stenotrophomonas maltophilia from dog - Petrzik, Karel; Brázdová, Sára (Virus genes, 2023)
Stenotrophomonas maltophilia is a Gram-negative bacterium widely distributed in the environment and associated with nosocomial infections, pneumonia, and bacteremia in humans and other mammals. We have isolated and sequenced a new virus that lyses the S. maltophilia strain from a dog skin. The virus has a siphovirus-like morphology and a linear dsDNA genome 60,804 pb in length with terminal repeats, four tRNA genes, and 111 putative proteins. The annotated genes resemble the corresponding genes of some siphoviruses, but the unique genome arrangement and limited similarity of the encoded proteins suggest that this virus does not belong to any known genus. The virus uses zinc metallopeptidase for lysis of its host. This enzyme is active in the presence of Zn2+ or Mg2+ ions and maintains its bactericidal activity up to 50 °C. Both the virus itself and the endolysin specifically degrade only the host bacterial strain.
Keywords: savci; psi; Siphovirus; Stenotrophomonas maltophilia; Animals; Humans; Dogs; Bacteriophage; lidé; Zinc metallopeptidase; zvířata; Mammals; Novel genus; Endolysin